2010
DOI: 10.1111/j.1750-3841.2010.01675.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Theabrownin from Pu‐erh Tea on the Metabolism of Serum Lipids in Rats: Mechanism of Action

Abstract: Theabrownin (TB), one of the main bioactive components in pu-erh tea, has a significant blood lipid-lowering effect in hyperlipidemic rats. Therefore, it was hypothesized that TB would regulate the activity of key enzymes involved in lipid metabolism and accelerate the catabolism of exogenous cholesterol in rats fed a high fat diet. A total of 90 Sprague-Dawley rats were randomly divided into a normal control group (Group I), a high fat diet group (Group II), and high-fat diet plus TB group (Group III). A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
81
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(83 citation statements)
references
References 10 publications
2
81
0
Order By: Relevance
“…Depending on their degree of fermentation, OTPs are known as theaflavins (TFs), thearubigin (TRs) and theabrownins (TBs) [17]. Theaflavins are the least oxidized tea polyphenols and are present in high concentrations in black tea, whereas theabrownins are highly oxidized tea polyphenols and the main bioactive component in pu-erh tea [18]. The TFs and TRs associated with black tea have been reported to have several health benefits, such as anti-obesity, hypocholesterolaemic and anti-diabetic properties [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on their degree of fermentation, OTPs are known as theaflavins (TFs), thearubigin (TRs) and theabrownins (TBs) [17]. Theaflavins are the least oxidized tea polyphenols and are present in high concentrations in black tea, whereas theabrownins are highly oxidized tea polyphenols and the main bioactive component in pu-erh tea [18]. The TFs and TRs associated with black tea have been reported to have several health benefits, such as anti-obesity, hypocholesterolaemic and anti-diabetic properties [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these spectroscopic and chemical results, the structure of yellow pigment 1 was determined as shown in Fig. 1 and named 4.63, H-7, H-7′), which were closely related to that of pinoresinol with a symmetric structure. 29) An important difference was observed in the aromatic region: two metacoupled aromatic doublets (H-2, H-2′) indicated the presence of a 3,4-dihydroxy-5-methoxy aromatic group.…”
Section: Resultsmentioning
confidence: 99%
“…In some parts of East Asia, aerobic and anaerobic microbial fermentation is applied to green tea or boiled tea leaves to produce tea products, which also decrease catechin concentrations. Although the importance of catechin degradation products has been reported recently, [2][3][4] little is known about the chemistry of products in fermented tea because of their complexity. Our research group has reported studies of enzymatic oxidation of catechins in black tea production [5][6][7] and hydrogenation of catechins in anaerobic microbial fermentation of green tea.…”
mentioning
confidence: 99%
“…Flavonoids [16], theabrownin (TB) [17,18], gallic acid (GA) [19], and statin [20] have anti-obesity/hypolipidemic effects and regulate lipid metabolism. Caffeine (CAF) [21] and polysaccharides [22,23] have blood glucose-lowering effects, and 8-C N-ethyl-2-pyrrolidinone substituted flavan-3-ols [24], ethanol-soluble pigment [25], polysaccharides [23,26], and phenolic compounds [27] (including GA, (+)-catechin, (-)-epicatechin, (-)-epicatechin-3-O-gallate, (-)-epigallocatechin-3-O-gallate (-)-epiafzelechin-3-O-gallate, kaempferol, and quercetin) have antioxidant properties.…”
Section: Introductionmentioning
confidence: 99%